Reputation and its measurement. An institutional approach - Adamska, Agata; Dąbrowski, Tomasz J. (Annales. Etyka w Życiu Gospodarczym, 2019)
The article deals with the issue of identifying and measuring institutions. As an example, reputation was taken into consideration. The analysis leads to the conclusion that reputation could be treated as an institution and could be measured in the context of its impact on economic outcomes. This measurement can be carried out at three levels of detail: micro, meso and macro, among these the third is the least recognised in new institutional economics.